RESTORATIVE JUSTICE IN CRIMINAL LAW AND ISLAMIC LAW: A COMPARATIVE ANALYSIS - Gunawan Widjaja; Adrian Bima Putra (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This article conducts a comparative analysis between the concept of restorative justice in modern criminal law and Islamic law. Restorative justice is an approach in the legal system that prioritises the restoration of the relationship between the victim and the offender as well as reparation for the harm suffered by the victim. In modern criminal law, this approach focuses on mediation and dialogue that aims to reduce recidivism and restore balance in society. On the other hand, Islamic law also has similar mechanisms through the concepts of sulh (peace) and diyya (compensation) which emphasise the importance of forgiveness and reconciliation. Despite differences in cultural and normative contexts, both legal systems demonstrate that restorative justice principles can be an effective and humane alternative in the handling of legal offences. As such, the integration of these principles is expected to contribute to the establishment of a more just and harmonious justice system.